Manajemen Sumber Daya Alam melalui Teknik Konservasi Tanah untuk Efisiensi Penggunaan Air di Lahan Kering - Wismaria Telaumbanua; Dermawan Zebua (CV. SINAR HOWUHOWU, 2026)
Population growth drives an increase in the intensity of land management in the upstream watershed area, both inside and outside the forest area, which has the potential to have a negative impact on the hydrological conditions of the watershed. Therefore, innovation is needed in the development of integrated land and water resource conservation programs, based on community settlement groups, and synergized with poverty alleviation programs to improve community welfare. This study uses the Systematic Literature Review (SLR) approach as its main method. Literature review is a systematic process that involves tracing, collecting, and analyzing data from various relevant library sources. In this context, the type of research applied is descriptive research, which aims to provide a comprehensive picture of the phenomena being studied. Soil is an important part of the earth system that plays a role in maintaining the function, change, and stability of ecosystems. The selection of soil cultivation methods must consider the level of soil density and porosity to ensure optimal soil structure for plants. One of the innovations that continues to be developed is soil conservation techniques that are specific to acidic drylands. Soil conservation must consider local knowledge because of its significant impact on increasing soil and plant productivity. Soil conservation techniques have a significant positive impact on the efficiency of water use in drylands. The application of techniques such as terracing, planting parallel to contours, and the use of organic ground cover can reduce water loss through surface flow and increase water infiltration into the soil. Soil moisture that is maintained longer through soil conservation allows plants to get a more stable water supply, especially in the dry season.